Pseudouridimycin: The First Nucleoside Analogue That Selectively Inhibits Bacterial RNA Polymerase. Issue 43 (12th September 2017) - Chellat, Mathieu F.; Riedl, Rainer
Abstract : Seek, and ye shall find : After years of focusing research on synthetic antibiotics out of fear that all the useful natural ones had already been found, a novel antibacterial compound has been discovered through conventional microbial extract screening. The broad‐spectrum nucleoside‐analogue inhibitor pseudouridimycin is selective for bacterial RNA polymerase and elicits very low resistance rates.